The Knowledge, Attitude, Practices, and Satisfaction of Non-Invasive Prenatal Testing among Chinese Pregnant Women under Different Payment Schemes: A Comparative Study - Zhu, Wenjun (Int J Environ Res Public Health, 2020)
Non-invasive prenatal testing (NIPT) for aneuploidy screening has been widely applied across China, and costs can affect Chinese pregnant women’s choices. This study aims to assess the knowledge, attitude, practices (KAP) and satisfaction regarding NIPT among pregnant women in China, and to further explore the relationship between payment schemes and women’s acceptability of and satisfaction with NIPT. A questionnaire survey was performed in Shenzhen and Zhengzhou, China, which separately applied “insurance coverage” and “out-of-pocket” payment scheme for NIPT. The major differences between the two cities were compared using chi-square test, Wilcoxon rank sum test, and propensity score matched analysis. Logistic regression models were applied to explore predictors for women’s acceptability and satisfaction. Compared with Zhengzhou participants, a higher proportion of Shenzhen women had heard of NIPT (87.30% vs. 64.03%), were willing to receive NIPT (91.80% vs. 80.43%) and had taken NIPT (83.12% vs. 54.54%), while their satisfaction level was lower. Having NIPT-related knowledge was associated with higher acceptability, and receiving genetic counseling helped to improve satisfaction. Besides, women with higher annual household incomes were more likely to take and be satisfied with NIPT. In conclusion, more attention should be paid to health education, subsidies for NIPT, and genetic counseling.